WORK FAMILY CONFLICT AND JOB SATISFACTION OF FEMALE LECTURERS: THE ROLE OF SELF-EFFICACY IN HIGHER EDUCATION HUMAN RESOURCE MANAGEMENT - Hariza Hasyim; Yanti Ernalia; Aras Aira (Jurnal Al-Iqtishad, 2025)
This study examines the impact of work–family conflict on female lecturers’ job satisfaction, with self-efficacy considered as a mediating variable, from the perspective of Human Resource Management (HRM) in higher education. A quantitative survey was conducted involving 64 married female lecturers with permanent status at UIN Sultan Syarif Kasim Riau, selected through purposive sampling. Data were analyzed using multiple linear regression and path analysis with SPSS software.The findings reveal that work–family conflict significantly and negatively influences both self-efficacy and job satisfaction, while self-efficacy positively affects job satisfaction. However, self-efficacy was not confirmed as a mediating variable between work–family conflict and job satisfaction. These results highlight the importance of gender-responsive HRM policies in higher education, particularly in workload regulation, organizational support, and psychological capacity-building for female lecturers. Such measures are crucial to enhance job satisfaction and sustain the implementation of the Tri Dharma of higher education.